2011
DOI: 10.1039/c0cp01803a
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties of liquid-filled shellac composite capsules

Abstract: This paper describes the mechanical properties of thin-walled, liquid-filled composite capsules consisting of calcium pectinate and shellac. In a series of experiments we measured the deformation of these particles in a spinning drop apparatus. For different pH-values we studied the elastic properties of these particles and compared the obtained results with the mechanical response measured by squeezing capsule experiments. In analogy to these experiments, we also investigated liquid-filled unloaded calcium pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
38
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 40 publications
(49 reference statements)
2
38
0
Order By: Relevance
“…Consequently, creation of composite systems by adding other components to a common system was considered like a simple method to enhance capsule properties [8]. In particular, composite vehicles containing both proteins and polysaccharides were a promising system and may advantageously use distinct functional characteristics of each compound [9].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, creation of composite systems by adding other components to a common system was considered like a simple method to enhance capsule properties [8]. In particular, composite vehicles containing both proteins and polysaccharides were a promising system and may advantageously use distinct functional characteristics of each compound [9].…”
Section: Introductionmentioning
confidence: 99%
“…In this work, we present investigations on polysaccharide solutions of sodium alginate with different cationic surfactants over a broad concentration range. Because of their environmental compatibility, biopolymers like gum acacia, chitosan, or alginate are found in pharmaceutical and food applications, in cosmetic products, and in detergents . Nevertheless, the use of biopolymers makes the study of polymer‐surfactant interactions more complicated because of a broader variation of the polymer chains (molecular weight, monomer sequence, branching, etc).…”
Section: Introductionmentioning
confidence: 99%
“…Because of their environmental compatibility, biopolymers like gum acacia, chitosan, or alginate are found in pharmaceutical and food applications, in cosmetic products, and in detergents. [34][35][36][37][38][39][40][41][42][43][44] Nevertheless, the use of biopolymers makes the study of polymer-surfactant interactions more complicated because of a broader variation of the polymer chains (molecular weight, monomer sequence, branching, etc). However, there are some important studies, [45][46][47][48] for example, the interesting hyaluronate-cationic surfactant complexes, which are investigated by Thalberg and Lindman, 49 or the carboxymethylcellulose-cationic surfactant complexes investigated by Langevin et al 50 Other important examples are the chitosan-anionic carboxylate surfactants studied by Chiappisi and Gradzielski 51 ; a good overview of the neglected class of surfactants with multiresponsive properties is given in Chiappisi.…”
Section: Introductionmentioning
confidence: 99%
“…Recently a systematic study of the thin-walled liquid-filled pectinate capsules with addition of shellac showed that precipitation of shellac under acidic conditions made the capsules softer and more flexible. [11] Xue et al [12] prepared and characterized calcium-shellac microspheres with added carbamide peroxide as tooth whitening agent. They used two technique based on dropping aqueous shellac solution into calcium chloride solution [12] and alternatively, emulsification of aqueous ammonium shellac solution in sunflower oil with calcium chloride powders [13].…”
Section: Introductionmentioning
confidence: 99%